Avaliação da dosagem dos tratamentos superficiais por penetração de rodovias baseada na exsudação e na perda de agregados - Silva, Raimi Costa da (2018)
In Brazil, chip seal is a widely used technique for coatings of Low Volume Traffic Highways. However its service specifications remain outdated and the national research in this area is scarce. In this context, the main objective of this thesis was to evaluate the design of the chip seals based on the occurrence of its two main distresses: aggregate loss and bleeding. For this purpose, the differences and limitations of the chip seals design processes recommended by DER / CE and DNIT were verified and chip seal samples (CSS) were produced in the laboratory according to the two specifications. In addition to the design method, the aggregate gradation, the temperature of the asphalt emulsion (46° C and 58° C) and the curing temperature (27° C and 50° C) were varied. The aggregate loss was evaluated by the Wet Track Abrasion Test and by the adapted Sweep Test, also relating its results to those of the Asphalt Bond Strength Test. In terms of bleeding evaluation, the Loaded Wheel Test was adapted and the digital image processing was applied to verify the bleeding area of the CSS. It has been found that the Aggregate Application Rate (AAR) and the Emulsion Application Rates (EAR) recommended by the agencies are incoherent and that the DNIT design is susceptible to the occurrence of the aggregate loss due to its high AAR. The results obtained showed that the application temperature of the emulsion should be selected based on the curing conditions of the construction site, in order to avoid waste of energy for a heating which will not bring significant benefits to the performance of the coating. It was also observed that the use of more uniform aggregates improves the quality of the chip seals without having to increase the temperature of application of the emulsion. Finally, it was concluded that bleeding is a distress more unlikely to occur in the chip seals designed by the design procedures studied, since both recommend low EAR and high AAR.